2004
DOI: 10.1177/039139880402700811
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Improved Water Quality on Inflammatory Markers in Patients Undergoing Regular Dialysis

Abstract: Hemodialysis utilizes large quantities of water for the preparation of dialysis fluid. Such water meets national standards and international standards but a considerable disparity exists between such standards with respect to microbiological purity. This study collated and retrospectively analyzed the impact of upgrading water systems from that specified in the US standards to those specified in European standards on clinical measures associated with inflammation in four metropolitan dialysis units for two per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 20 publications
0
35
0
1
Order By: Relevance
“…Retrospective analysis on the effects of improved water quality in the USA reported that the upgrading water systems from that specifi ed in the US standard (1-2 EU/ml) to those specifi ed in European standards ( ! 0.06 EU/ml) was associated with the decrease in CRP and the increases in hemoglobin and serum albumin [33] , suggesting the 1-2 EU/ml level of endotoxin in dialysate is inappropriately high. In our study we demonstrated that 0.055-0.064 EU/ml of endotoxin enhances the infl ammatory response and the formation of ␤ 2 MG and pentosidine during hemodialysis.…”
Section: Discussionmentioning
confidence: 98%
“…Retrospective analysis on the effects of improved water quality in the USA reported that the upgrading water systems from that specifi ed in the US standard (1-2 EU/ml) to those specifi ed in European standards ( ! 0.06 EU/ml) was associated with the decrease in CRP and the increases in hemoglobin and serum albumin [33] , suggesting the 1-2 EU/ml level of endotoxin in dialysate is inappropriately high. In our study we demonstrated that 0.055-0.064 EU/ml of endotoxin enhances the infl ammatory response and the formation of ␤ 2 MG and pentosidine during hemodialysis.…”
Section: Discussionmentioning
confidence: 98%
“…The treatment of patients with ultrapure dialysate is reported to improve nutritional status, increase responsiveness to erythropoietin, slow the decline in residual renal function, lessen cardiovascular morbidity, and decrease the incidence of ␤ 2 -microglobulin amyloidosis. Moreover, observational studies suggest a link between clinical outcomes and dialysate purity [23][24][25][26][27][28][29] .…”
Section: Evidence That Improved Water Quality Mattersmentioning
confidence: 99%
“…Most of these reports have shown that ultrapure dialysate use might lead to better outcomes. [14][15][16][17] However, no study has investigated the effect on survival in a randomized, controlled manner. This study showed no difference between the ultrapure and standard dialysate groups in the primary analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] In the multicenter European Membrane Permeability Outcome (MPO) Study, subgroup analyses showed better survival rates with highflux HD in patients with hypoalbuminemia and patients with diabetes. 12 Ultrapure dialysis fluid has also been associated with less inflammation, resulting in clinically relevant improvements, including amelioration of erythropoietin response, 13 better nutritional status, 14,15 and reduction in the incidence of b 2 -microglobulin amyloidosis. 16 Although preliminary reports suggested lower cardiovascular morbidity with the use of ultrapure dialysis fluid, 17 no randomized and controlled trial has been performed addressing hard clinical outcomes.…”
mentioning
confidence: 99%